WEB-BASED CAFE SEARCH APP USING BOOTSTRAP IN THE CITY OF SURABAYA - Syarifuddin Agin Saputra; Eman Setiawan (Universitas Trunojoyo Madura, 2022)
Competition in the world of industrial trade 4.0 is currently getting bigger because of technology and humans must be faced with online-based technology that makes it easier for them to carry out their activities. In addition, the increasing number of visitors, especially cafes in the city of Surabaya. Because it is not strategic, it makes the cafe so few visitors and only residents who often pass the cafe. With the media so that the cafe can be known by many people, namely the existence of a café search application in the city of Surabaya can help introduce cafes easily. In developing the cafe search application in the city of Surabaya, it is web-based and will use the Bootstrap framework which is useful to speed up and simplify application development. Framework is a framework for web-based and desktop-based applications that serves to improve website security, make code programs more structured, and help developers perform more efficiently. By using the waterfall method or commonly called the waterfall method in order to be able to support to minimize errors that may occur because the process is carried out one by one.